The use of oxybutynin for treating facial hyperhidrosis O uso da oxibutinina no tratamento da hiperidrose facial - Nelson Wolosker; José Ribas Milanez de Campos; Paulo Kauffman; Marco Antonio Munia; Samantha Neves; Fábio Biscegli Jatene; Pedro Puech-Leão (Sociedade Brasileira de Dermatologia, 2011)
BACKGROUND: Facial hyperhidrosis is a disease that may lead patients to serious emotional disturbances. Video-assisted thoracic sympathectomy provides excellent resolution of facial hyperhidrosis, but is associated with certain complications. The most frequent and important complication is compensatory hyperhidrosis. Especially in patients who have undergone resection of the second thoracic ganglion, the risk of severe compensatory hyperhidrosis is higher, which may cause dissatisfaction with the procedure. OBJECTIVE: The aim of this study was to evaluate the efficacy of the use of low doses of oxybutynin in treating facial hyperhidrosis as well as the level of patient satisfaction with its use. METHODS: 25 patients with facial hyperhidrosis were treated with oxybutynin. The patients underwent 2 evaluations: before and after treatment. These evaluations were used to assess the patients' clinical improvement and quality of life. RESULTS: We observed that more than 75% of the patients evolved with an improvement in facial hyperhidrosis, and 52% of them presented a great improvement. CONCLUSION: Treatment of facial hyperhidrosis with oxybutynin is a good alternative to sympathectomy, since it presents good results and improves quality of life, in addition to not exposing patients to the risk of experiencing the side effects of sympathectomy FUNDAMENTOS: Hiperidrose facial é uma doença que pode levar os pacientes a sérios distúrbios emocionais. A simpatectomia torácica vídeo-assistida proporciona excelente resolução da hiperidrose facial, mas está associada a algumas complicações, sendo a mais freqüente e mais importante a hiperidrose compensatória. Especialmente em pacientes submetidos à ressecção do segundo gânglio torácico, o risco de hiperidrose compensatória grave é maior, o que pode causar insatisfação com o procedimento. OBJETIVO: O objetivo deste estudo foi avaliar a eficácia e a satisfação dos pacientes com o uso da oxibutinina em doses baixas para tratar a hiperidrose facial em uma série grande de pacientes. MÉTODOS: 25 pacientes com hiperidrose facial foram tratados com oxibutinina. Os pacientes foram submetidos a duas avaliações: antes e depois do tratamento. Estas foram usadas para avaliar a melhoria clínica e a qualidade de vida. RESULTADOS: Observou-se que mais de 75% dos pacientes evoluíram com melhora na hiperidrose facial, sendo que 52% deles apresentaram uma grande melhora. CONCLUSÃO: O tratamento da hiperidrose facial com oxibutinina é uma boa alternativa à simpatectomia, visto que apresenta bons resultados e melhora a qualidade de vida, e os pacientes não correm o risco dos efeitos colaterais da simpatectomia